Feasibility study of the use of antiprotons and other heavy particles in therapeutic and diagnostic applications - Kantemiris, I.; Angelopoulos, A.; Giokaris, N.; Kalogeropoulos, T.; Sakelliou, L.; Dubnicka, S.; Dubnickova, A. Z.; Fulop, M.; Ruzicka, J. (HNPS Advances in Nuclear Physics, 2020)
N/A